Validation of free-convective heat transfer analysis with JUPITER to evaluate air-cooling performance of fuel debris in dry method - Shinichiro UESAWA (The Japan Society of Mechanical Engineers, 2018)
A dry method is one of fuel debris retrieval methods for decommissioning of TEPCO’s Fukushima Daiichi nuclear power station. However, the cooling of fuel debris must be fully maintained without water. Japan Atomic Energy Agency (JAEA) has evaluated the air-cooling performance of the fuel debris in the dry method by using JUPITER. Because JUPITER can represent the relocation of the corium, the unknown parameters, such as the composition and the position of the fuel debris at the RPV pedestal, can be reduced. By calculating the heat transfer of the fuel debris based on the corium relocation obtained with JUPITER, more accurate analysis of the air-cooling performance of the fuel debris in the dry method is expected. In order to evaluate the air-cooling performance of fuel debris in the dry method by using JUPITER, the validation of the free-convective heat transfer analysis of JUPITER were performed in this paper. In order to qualitatively evaluate results of JUPITER for configurations closer to experimental conditions and to decide physical values and positions to be measured in the validation, JUPITER was compared with OpenFOAM for the simple cuboid configuration which has the heating and cooling surfaces at the floor and the ceiling, respectively. The comparison proved that JUPITER can calculate the vertical temperature distribution as well as OpenFOAM on the condition of the lower heating amount. In the validation, JUPITER was compared with the heat transfer experiments of free convection in air adjacent to an upward-facing horizontal heating surface. The comparison proved that JUPITER was in good agreement with the experiment on the condition of the lower heating-surface temperature. The result indicated that JUPITER is a helpful numerical method to evaluate the free-convective heat transfer of the fuel debris in the dry method.